Occurrence and distribution characteristics of PCBs and PBDEs in farmland soils adjacent to electronic circuit board dismantling ruins - Zhang, Zhen; Chen, Lin Hua; Tao, Min Long; Zhou, Dan Dan; Zhang, Yuan; Yao, Jun; Kong, Qing Na; Guo, Bin Bin (Frontiers in Environmental Science, 2023)
The Nanwan village, a green ecological village in Taizhou city, is used as a recycling area (recycling for heavy metal) for electronic circuit boards and as crushing and stacking sites of waste circuit boards for nearly 20 years from 1980s to 2000s. At present, although the e-waste recycling activities in Taizhou city have been effectively controlled, and many areas polluted by the e-dismantling activities have been gradually remediated except Nanwan village. Nanwan village seems to have been forgotten for its special geographical location, which has attracted our attention because of its ecological and food safety issues. Accordingly, the content of polychlorinated biphenyls (PCBs) and polybrominated diphenyl ethers (PBDEs) in the surface soil around the ruins and four edible agricultural crops were investigated. The main conclusions are as follows: among the four dismantling ruins and surrounding soil samples investigated, the content of Σ20PCBs in vegetable field topsoil of 2(20) is 1321.3 ± 132.1 μg kg−1; the content of Σ8PBDEs in the paddy soil of 3(1S) is 7216.9 ± 232.0 μg kg−1; biological toxicity events are likely to occur frequently in 2(20) and 3(1S). PCBs and PBDEs have both horizontal diffusion in distance and vertical diffusion in depth. The lifetime carcinogenic and non-carcinogenic risks of PCBs and PBDEs are at a low risk level, except for the non-carcinogenic risk of PCBs for children in 3(1S). The lifetime carcinogenic and non-carcinogenic risks of PCBs and PBDEs in the edible parts of garlic, ginger, mung beans, and oranges were all at acceptable or negligible levels.